Determinants of the continuous purchase intention towards epidemic prevention products among Malaysia’s adult post-pandemic - Chi, Lin Ching; Chia, Xin Yan (2023)
Due to the Covid-19 outbreak, the public is becoming concerned the safety and health, at the same time, they will take preventive steps in order to carry out their daily activities. However, Malaysians are slowly turning away from masks and other epidemic prevention products, including hand sanitizer and face shields as the number of confirmed Covid-19 cases has decreased. Meanwhile, Malaysians are willing to take prevention activities in order to protect themselves from the crowd as well as protect themselves from being reinfected. Therefore, numerous factors encourage us to focus on investigating the continuous purchase intention towards epidemic prevention products. Our research responds to the need for determinants of the continuous purchase intention towards epidemic prevention products among Malaysia’s adults post-pandemic. Throughout the research study, Theory of Planned Behavior was applied in this research study in order to discover the reason for motivating such continuous purchase intention. There are four independent variables were proposed in this research for the purpose of examining several hypotheses and effect of these variables on Malaysian adults’ continuous purchase intention towards epidemic prevention goods. In this research, the sample size is 297 people who aged 18 and above as the targeted respondents. The result from the four hypotheses confirms that attitude (ATT), subjective norm (SN), perceived behavioural control (PBC) and health concern are vital in affecting Malaysian adults’ continuous purchase intention towards epidemic prevention goods post pandemic.